2014
DOI: 10.1097/eja.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ketamine on hypoventilation during deep sedation with midazolam and propofol

Abstract: clinicaltrials.gov identifier: NCT01535976.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Studies demonstrated that ketamine, when combined with other sedative medications, mostly propofol, may decrease respiratory-related adverse effects. 194 , 195 One such prospective observational study looking at sedation-related risk factors (airway obstruction, hypoventilation, and desaturation) for procedural sedation found ketamine to be a protective factor. 195 De Oliveira et al 194 reported that ketamine decreased duration and severity of hypercapnia in patients undergoing breast surgery under deep sedation.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
“…Studies demonstrated that ketamine, when combined with other sedative medications, mostly propofol, may decrease respiratory-related adverse effects. 194 , 195 One such prospective observational study looking at sedation-related risk factors (airway obstruction, hypoventilation, and desaturation) for procedural sedation found ketamine to be a protective factor. 195 De Oliveira et al 194 reported that ketamine decreased duration and severity of hypercapnia in patients undergoing breast surgery under deep sedation.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
“…It is important to realise that we and others observed a ketamine-induced stimulatory effects on breathing at subanaesthetic ketamine doses. 13,15 In rats, Eikermann and colleagues 14 showed that respiratory stimulation persists even at anaesthetic doses, while Hamza and colleagues 35 found the reverse in children. Further human studies are needed to fully understand the complex behaviour of the low-and high-dose ketamine isomers on breathing.…”
Section: Esketamine-and Racemic Ketamine-induced Stimulation Vs Deprementioning
confidence: 99%
“…In a study of 54 women undergoing breast surgery, severe hypoventilation was found to be significantly lower (0% vs 28%) in patients who received ketamine in addition to propofol and midazolam for procedural sedation. 10 This evidence may suggest that, in our patient, the beneficial effects observed may be due to ketamine administration enhancing the effects of opioids. However, it is difficult to apply data from noncritically ill women undergoing elective surgery to our patient, as ketamine may have varying effects based upon numerous factors including gender, critical illness, and use of concurrent medications.…”
Section: Discussionmentioning
confidence: 62%